Types of psychological help-seeking as a result of the Corona Virus pandemic (Covid 19) among individuals in the Sultanate of Oman - Almanwari, Issa Mohammed; Alkalbani, Said Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to uncover patterns of seeking psychological help and its relationship to gender, type of housing and age as a result of the Corona Virus (Covid 19) pandemic among individuals in the Sultanate of Oman. The study sample consisted of (384) male and female individuals who were chosen in a stratified random manner. The study used the descriptive method to collect data and use the questionnaire as a study tool. The results of the study showed that avoiding the request for psychological aid (self-efficacy) is the most appreciated form of individuals for the types of psychological aid request, followed by the request for instrumental help, then avoiding the request for help (show inefficiency). The results also revealed statistically significant differences at the level of significance (α = 0.05) in avoiding seeking help (showing inefficiency) in favor of (females), and statistically significant differences in the same axis in favor of the age group (18-30) among all members of the sample. The study also showed that there were no differences between the patterns of seeking psychological help due to the variable type of housing (city / village). The study recommended taking care to educate the community and create a safe and secure environment towards seeking psychological help, and its importance in solving the psychological problems of the individual and society.
Keywords: psychological help-seekin; help-seekin; Covid 19; oman